The Influence Of Product Quality, Service Quality, Price And Brand Image On Shopee Customer Satisfaction - Deprian, Agus; Widanti, Afrima (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Purpose – This paper seeks to examine the influence of product quality, service quality, price and brand image on shopee customer satisfaction survey in Bengkulu province. Methodology/approach – The data collection method used in this research is the direct or self-administered data collection method, namely the distribution method by distributing online questionnaires to obtain information from respondents. Distribution of questionnaires was carried out by distributing questionnaires online to respondents via social media such as WhatsApp, Instagram and assisted by closest friends in distributing questionnaires. This research collected a sample of 309 respondents.. Findings – It was found that . Good quality, low prices, good brand image and good service quality can increase the satisfaction of customers who shop at Shopee in the community in the city of Bengkulu and have a positive and significant influence. Novelty/value – because product quality, price, brand image and service quality have an influence on customer satisfaction, so it is important for companies to evaluate further the variables that form customer satisfaction to make customers more satisfied. Keywords Because product quality, price, brand image and service quality have an influence on customer satisfaction, it is important for companies to evaluate further the variables that form customer satisfaction to make customers more satisfied. keywords service quality, product quality, price brand image.